A Rationale for the Use of F18-FDG PET/CT in Fever and Inflammation of Unknown Origin. (17th December 2012) - Balink, H.; Verberne, H. J.; Bennink, R. J.; van Eck-Smit, B. L. F.
Abstract : This review focuses on the diagnostic value of hybrid F18-FDG Positron Emission Tomography/Computerized tomography (PET/CT) in fever of unknown origin (FUO) and inflammation of unknown origin (IUO). Due to the wide range of possible causes both FUO and IUO remain a clinical challenge for both patients and physicians. In addition, the aetiology of IUO shows the same variation in diseases as the FUO spectrum and probably requires the same diagnostic approach as FUO. There are numerous historically used diagnostic approaches incorporating invasive and non-invasive, and imaging techniques, all with relative high specificity but limited sensitivity. This hampers the generalization of these diagnostic approaches. However, recently published reports show that F18-FDG PET/CT in FUO and IUO has a high sensitivity and a relative non-specificity for malignancy, infection and inflammation. This makes F18-FDG PET/CT an ideal diagnostic tool to start the diagnostic process and to guide subsequent focused diagnostic approaches with higher specificity. In addition, F18-FDG PET/CT has a relative high negative predictive value. Therefore F18 FDG PET/CT should be incorporated in the routine diagnostic work-up of patients with FUO and IUO, preferably at an early stage in the diagnostic process.